A comparative study on characterisation of ASS 316L at room and sub-zero temperatures. Issue 4 (2nd October 2021) - Dharavath, Baloji; Lade, Jayahari; Varmaa, Dinesh; Singh, Swadesh Kumar; Naik, M.T.
ABSTRACT: Austenitic Stainless Steel 316 L grade has wide applications in industries like pharmaceutical, chemical, petrochemical, medical equipment, and many specific subzero temperature products. These subzero applications are increasing in modern-day products to solve many issues like Natural gas storage and transport and many more. It is an ideal material for these applications due to its superior properties at these operating temperatures. In the present investigation tensile tests for ASS316 L material is conducted by considering the various parameters like different temperatures (room temperature(RT), 0°C, −25°C, −50°C) along with different orientation (0°, 45°, 90°), and crosshead speeds (3, 5 and 7 mm/min). The temperature variation was achieved by regulating the liquid CO2 cylinder connected using a pipe system to the closed furnace of the Universal Testing Machine setup is electronic controlled system. The output data were used to analyse the Mechanical Characteristics of the material. Then the fractured specimens at the room temperature and sub-zero temperatures were studied and analysed the failure modes in the material for the above changing variables. It was observed that the failure mode is changing from a ductile fracture to brittle when decreasing the temperature below zero degrees centigrade as predicted.